The Gambia - Improving Civil Service Performance : Main Analysis - World Bank (World Bank, 2012)
There is a general consensus that The Gambia's civil service has a number of key capacity weaknesses. Pay is too low to hire, motivate and retain key technical and professional staffs. Staffs are not managed to achieve results, neither rewarded for good performance nor sanctioned for poor performance or breaking the rules. Frequent removals and transfers of Government officials have undermined job security and institutional knowledge. The main objective of this report is to outline the results of the analysis of civil service capacity constraints. Based on the analysis, the report presents options to consider for the proposed civil service reform program which the Government plans on preparing. The Personnel Management Office (PMO) drafted a reform strategy in August 2007, the 'public sector reform sector strategy paper 2007-2011,' which can be further developed by incorporating the findings of report. The expected goal of this strategy is to build the capacity of the civil service to formulate policies and allocate resources to implement those policies so as to ensure effective delivery of public services. This report is organized as follows: chapter one identifies the overall capacity constraints in the civil service; chapter two analyzes civil service pay and benefits; chapter three assesses human resource management; chapter four focuses on the education and health sectors; and chapter five summarizes the major findings and proposes reform options and the next steps.